ChemInform Abstract: Visible Light Photoredox‐Catalysed Intermolecular Radical Addition of α‐Halo Amides to Olefins. Issue 33 (19th August 2014) - Nakajima, Masaki; Lefebvre, Quentin; Rueping, Magnus
Abstract α‐Chloro amides are shown to be a new class of α‐acetyl radical precursors, which undergo photoredox‐catalyzed intermolecular α‐addition with various olefins exclusively in an anti‐Markovnikov fashion.